PENGARUH KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) UNIVERSITAS RIAU - Sri Lestari; Makhdalena Makhdalena; Hardisyem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of the research is to find out the influence of service quality to participation of Koperasi Pegawai Republik Indonesia University of Riau. This research is a quantitative research, with amount of population is 1.949 members and amount sample is 94 members. The method that used to gathering data is quisioner. Analysis data method uses descriptive analysis and multiple linier.The results showed that the quality of care consisting of realibility (X1), assurance (X2), emphaty (X3), tangible (X4), and tresponsiveness (X5), jointly have a positive influence.The results showed that service quality has a significant impact on the participation of members KPRI University of Riau, which amounted to 76%. Of the five variables that affect the participation of Members of KPRI University of Riau, the most dominant variable is a variable Empathy, has tcount (4.880)> t table (1,987) compared with the other variables, with significant requirements. Keywords :Participation, Quality of Service, Reliability, Assurance, Empathy, Tangible, responsiveness.